LY293558 prevents soman-induced pathophysiological alterations in the basolateral amygdala and the development of anxiety. (February 2015) - Prager, Eric M.; Figueiredo, Taiza H.; Long, Robert P.; Aroniadou-Anderjaska, Vassiliki; Apland, James P.; Braga, Maria F.M.
Abstract: Exposure to nerve agents can cause brain damage due to prolonged seizure activity, producing long-term behavioral deficits. We have previously shown that LY293558, a GluK1/AMPA receptor antagonist, is a very effective anticonvulsant and neuroprotectant against nerve agent exposure. In the present study, we examined whether the protection against nerve agent-induced seizures and neuropathology conferred by LY293558 translates into protection against pathophysiological alterations in the basolateral amygdala (BLA) and the development of anxiety, which is the most prevalent behavioral deficit resulting from exposure. LY293558 (15 mg/kg) was administered to rats, along with atropine and HI-6, at 20 min after exposure to soman (1.2 × LD50). At 24 h, 7 days, and 30 days after exposure, soman-exposed rats who did not receive LY293558 had reduced but prolonged evoked field potentials in the BLA, as well as increased paired-pulse ratio, suggesting neuronal damage and impaired synaptic inhibition; rats who received LY293558 did not differ from controls in these parameters. Long-term potentiation of synaptic transmission was impaired at 7 days after exposure in the soman-exposed rats who did not receive anticonvulsant treatment, but not in the LY293558-treated rats. Anxiety-like behavior assessed by the open field and acoustic startle response tests was increased in the soman-exposed rats at 30 and 90 days after exposure, while rats treated with LY293558 did not differ from controls. Along with our previous findings, the present data demonstrate the remarkable efficacy of LY293558 in counteracting nerve agent-induced seizures, neuropathology, pathophysiological alterations in the BLA, and anxiety-related behavioral deficits. Highlights: Soman exposure causes pathophysiological alterations in the basolateral amygdala. Soman exposure produces long-term anxiety. Post-exposure treatment with LY293558 prevents increases in paired-pulse ratio. Post-exposure treatment with LY293558 minimizes impairments in synaptic plasticity. Post-exposure treatment with LY293558 prevents the development of anxiety.